754 DEVELOPING A FRAILTY SERVICE IN ROYAL BOLTON HOSPITAL. (8th March 2022) - Connolly, A; Kallat, A; Cairns, M; Oates, R
Abstract: Introduction: Bolton NHS Trust has a busy Emergency Department (ED) in the North West. 21% of attendances are patients aged over 65. Early specialist input is recognised for frail older adults. The goal of this quality improvement project was to readdress the admission/discharge bias and to improve the quality of care for older patients in ED. A referral pathway would be implemented, and frailty team embedded into ED. Methods: Data was collected from November 2018 to January 2020. The Frailty service underwent multiple quality improvement plans using PDSA cycles. Absence of documentation of the Clinical Frailty Score (CFS) lead to inadequate identification of frailty in ED. Frailty ACPs were based in ED to develop inter-disciplinary working whilst delivering education programmes to staff. In conjunction, Consultant-led sessions were delivered to ED trainees. This intervention was assessed by auditing CFS within patient electronic notes. Subsequent PDSA cycles resulted in CFS posters displayed in ED, in conjunction with a referral pathway to identify suitable patients. CFS scores became embedded in electronic patient records. Geriatricians reviewed directly into ED. Interventions were evaluated. Results: Documentation of CFS increased by 20%. Referrals increased from 0 in November 2018 to 147 in December 2020. In December 2020, 52% of the patients assessed by the Frailty team were discharged, 46% of those had been referred to medicine. During the study period, the referral criteria was unreliably followed. Often referrals followed informal discussions rather than the criteria pathway. Inclusion criteria was restrictive. Education sessions were well received. Conclusion: Basing the frailty team into ED encouraged documentation and recognition of CFS. Repeated education sessions are required due to staff turnover. Geriatrician review within ED reduced admissions to medical beds. The referral pathway has been adapted and extended to Community partners. This intervention is ongoing and will require evaluation.